Kontribusi Kurikulum Merdeka dalam Upaya Peningkatan Kemampuan Literasi di Indonesia - Rosadi, Nicky; Megayanti, Windi (Universitas Indraprasta PGRI, 2024)
This research aims to discuss the contribution of the Kurikulum Merdeka to efforts to increase literacy skills in Indonesia. The method used in this research is a qualitative method using a literature review. The object of this study is the contribution of the Kurikulum Merdeka to efforts to increase literacy skills in Indonesia. Based on the studies conducted, it is known that there are several Kurikulum Merdeka programs that contribute to efforts to improve literacy skills. These programs are in the form of (1) Cross-Curriculum Literacy; (2) Learning Indonesian; (3) The Role of Teachers and Literacy Programs; (4) Extensive Reading Program; and (5) The Importance of Local Wisdom and Contextual Learning. Therefore, it can be concluded that the implementation of the Kurikulum Merdeka is an important step in efforts to improve the quality of education in Indonesia, especially in terms of literacy skills. Even though the results cannot be seen immediately, it is hoped that with more flexible and contextual learning strategies, Indonesian students' literacy skills will improve over time.